Argentina: as a host country of Chinese investments for the development of video games (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2020)
This paper intends to describe the current situation of Foreign Direct Investment (FDI) flows in Argentina between the years 2014-2018, and discusses related opportunities and challenges for investing in the country in videogames development. We provide a comprehensive analysis using the data of the World Bank, United Nations, INDEC, OECD among others; intending to clarify the positive and negative effects of investing in Argentina as a host country for video games development. We support the view of the Association of Argentine Video Game Developers (ADVA) that says that the video games industry has had a strong development in Argentina in the last decade, arguing that Argentina owns the majority of tech unicorns in Latin America. This is a well-connected resource, particularly in satisfying domestic consumption and the achievement of exporting by working for overseas companies. Although video games development has helped to improve economic performance in the country, we find that the recent dependence on foreign financing may spark other problems because of the instability of investments in Argentina and the continuously changing market could produce uncertainty in the domestic growth. Moreover, the increasing dependence of outsources and the lack of government financing could lead also to the slow growth of the sector itself.
Keywords: international markets, video¬games industry, Argentina, China, FDI.